2015
DOI: 10.1186/s12870-015-0532-3
|View full text |Cite
|
Sign up to set email alerts
|

OsGRAS23, a rice GRAS transcription factor gene, is involved in drought stress response through regulating expression of stress-responsive genes

Abstract: BackgroundDrought is a major abiotic stress factors that reduces agricultural productivity. GRAS transcription factors are plant-specific proteins that play diverse roles in plant development. However, the functions of a number of GRAS genes identified in rice are unknown, especially the GRAS genes related to rice drought resistance have not been characterized.ResultsIn this study, a novel GRAS transcription factor gene named OsGRAS23, which is located in a drought-resistant QTL interval on chromosome 4 of ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 60 publications
3
145
0
1
Order By: Relevance
“…Drought induces expression of OsABF1 , which directly binds to the downstream promoter of OsWARKY104 to activate its expression, which in turn, inhibits expression of Ehd1 and delays flowering (Zhang et al ., ). Previous studies have shown that the Lilium longiflorum SCR‐like (LISCL) subfamily proteins may be involved in the stress response, and recently, OsGRAS23, a member of the LISCL subfamily of rice, has been reported to be involved in drought response (Xu et al ., ). We observed that the dhd1 dhd1 l double mutant flowered earlier than WT and the dhd1 single mutant under drought and salt treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Drought induces expression of OsABF1 , which directly binds to the downstream promoter of OsWARKY104 to activate its expression, which in turn, inhibits expression of Ehd1 and delays flowering (Zhang et al ., ). Previous studies have shown that the Lilium longiflorum SCR‐like (LISCL) subfamily proteins may be involved in the stress response, and recently, OsGRAS23, a member of the LISCL subfamily of rice, has been reported to be involved in drought response (Xu et al ., ). We observed that the dhd1 dhd1 l double mutant flowered earlier than WT and the dhd1 single mutant under drought and salt treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Two Arabidopsis Phytochrome A signal transduction (AtPAT) subfamily members, Chitin-Inducible Gibberellin-Responsive 1 (CIGR1) and CIGR2, are responsive to N-acetyl-chitooligosaccharide elicitor and GA (Day et al, 2004). Recently, OsGRAS23 was reported to be involved in drought stress response by regulating expression of stress-responsive genes (Xu et al, 2015). However, GRAS proteins have not been reported in connection with heading date in rice.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus very difficult to enhance the drought-tolerance in rice by regulating a single gene. Instead, DEGs which could cause systematic effects have been preferred to be selected and applied in drought-tolerance breeding (Luo, 2010; Hu and Xiong, 2014), such as transcript factors (Hu et al, 2006; Jeong et al, 2012; Fang et al, 2015; Xu et al, 2015) and protein kinases (Saijo et al, 2000; Ning et al, 2010). Similarly, the metabolism of a metabolite commonly results from interactions of many genes and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We validated the measured levels of gene expression via the qPCR method, as previously described by Xu et al (2015). Nine genes, including known drought-resistance genes and several candidate genes were selected for validation (Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…(MONOCULM 1, a gene that is important in the control of rice tillering) (Li et al, 2003), SLR1 (the gene associated with the slender phenotype and its product is an intermediate of the GA signaling pathway) (Ikeda et al, 2001), SCR (SCARECROW, an essential gene for the asymmetric division of the cortex/endodermis progenitor cell in the root) (Kamiya et al, 2003), DLT (dwarf and lowtillering gene) (Tong et al, 2009), and OsGRAS19 , have been well characterized, while the functions of other rice GRAS genes are largely unknown (Xu et al, 2015). According to the report provided by Xu and coworkers (2015), OsGRAS23, a stress-responsive GRAS transcription factor, positively regulates the drought tolerance in rice through the induction of several stress-responsive genes.…”
Section: Identification Of Genes Encoding the Transcription Factormentioning
confidence: 99%